2021
DOI: 10.1021/acs.est.1c00509
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Chemical Proteomics Reveals Interspecies Variations on Binding Schemes of L-FABP with Perfluorooctanesulfonate

Abstract: Evaluating interspecies toxicity variation is a long-standing challenge for chemical hazard assessment. This study developed a quantitative interspecies thermal shift assay (QITSA) for in situ, quantitative, and modest-throughput investigation of chemical–protein interactions in cell and tissue samples across species. By using liver fatty acid binding protein (L-FABP) as a case study, the QITSA method was benchmarked with six per- and polyfluoroalkyl substances, and thermal shifts (ΔT m) were inversely related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Then, we performed molecular docking to better understand the structure-related interactions between hydrocarbon surfactants and L-FABP. Taking dodecyl benzenesulfonate as an example, three hydrogen bonds were formed between the negatively charged sulfonate group and residues of Arg-122, Ser-39, and Ser-124 (Figure S7), which was similar to results previously reported for PFAS. ,, In addition, the alkyl chain formed hydrophobic contacts with the interior cavity of L-FABP. It has been demonstrated that both the hydrogen bond and the hydrophobic interactions are crucial in stabilizing the ligand-protein complex of L-FABP. , Since these hydrocarbon surfactants have similar acidic head groups (SO 3 – and SO 4 – ), the stronger hydrophobic effects of longer-chain hydrocarbon surfactants may explain their stronger binding affinities to L-FABP …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Then, we performed molecular docking to better understand the structure-related interactions between hydrocarbon surfactants and L-FABP. Taking dodecyl benzenesulfonate as an example, three hydrogen bonds were formed between the negatively charged sulfonate group and residues of Arg-122, Ser-39, and Ser-124 (Figure S7), which was similar to results previously reported for PFAS. ,, In addition, the alkyl chain formed hydrophobic contacts with the interior cavity of L-FABP. It has been demonstrated that both the hydrogen bond and the hydrophobic interactions are crucial in stabilizing the ligand-protein complex of L-FABP. , Since these hydrocarbon surfactants have similar acidic head groups (SO 3 – and SO 4 – ), the stronger hydrophobic effects of longer-chain hydrocarbon surfactants may explain their stronger binding affinities to L-FABP …”
Section: Resultssupporting
confidence: 90%
“…Taking dodecyl benzenesulfonate as an example, three hydrogen bonds were formed between the negatively charged sulfonate group and residues of Arg-122, Ser-39, and Ser-124 (Figure S7), which was similar to results previously reported for PFAS. 32,47,51 In addition, the alkyl chain formed hydrophobic contacts with the interior cavity of L-FABP. It has been demonstrated that both the hydrogen bond and the hydrophobic interactions are crucial in stabilizing the ligand-protein complex of L-FABP.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Up to now, there is sparse information on the interaction of the target PFASs with mouse L-FABP and serum albumin. Since mouse L-FABP (84.3%) 47 and serum albumin (72.4%) 48 have high identities with humans, we investigated the relationships between R L/S obtained from mice and log K d (hL-FABP) /log K d (HSA) , to further verify the competitive binding mechanisms in liver-blood partition. As expected, there were strong negative correlations between the R L/S and log K d (hL-FABP) /log K d (HSA) (Figure 3, Table S8, and Correlations 1 and 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[43][44][45] Furthermore, transcriptomic and proteomics analysis of zebrafish upon exposure to drugs or environmental factors can be easily performed to predict gene function related to specific phenotypes and to reveal gene networks and signalling pathways. 41,[46][47][48][49] Transcriptomics and proteomics analysis of the interleukin 6 (IL6)-overexpressed liver revealed a deregulation of glycolysis/gluconeogenesis pathway. 50 In addition, more research has linked metabolic processes to gene expression.…”
Section: Key Pointsmentioning
confidence: 99%